Empirical Study of Cross-Border E-commerce Brand Formation - Jing Zhang(장정); Ziyang Liu(유자양) (한국컴퓨터정보학회논문지, 2023)
Cross-border e-commerce has emerged as a crucial force in stabilizing China's foreign trade, driving the transformation and upgrade of China's foreign trade, and contributing to global economic development and stability. As a result, promoting the high-quality development of cross-border e-commerce has become a common challenge within the Chinese industry. However, with the rapid growth of cross-border e-commerce, it faces new phenomena and challenges, such as a mix of quality, fierce competition, and price competition. Brands serve as distinguishing markers for identifying entities, and brand building is a prudent choice for achieving high-quality development in cross-border e-commerce. This article utilizes brand theory, employing a combined qualitative and quantitative approach, with a specific focus on key elements within the operations of cross-border e-commerce enterprises. Through an analysis of the key elements influencing the formation and development of brands within the internal operations of Chinese cross-border e-commerce enterprises, it investigates their internal formation mechanisms and assesses the significance of these critical factors in influencing brand formation. The research process is based on data from overseas consumers, conducting empirical analysis, ultimately providing certain guidance for brand development in cross-border e-commerce enterprises. KCI Citation Count: 0